Pandemic Corona (Covid-19) and Health Law Protection - Birkah Latif (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pandemic Corona (Covid-19), which struck all countries in the world, not only caused anxiety but also thenumber of victims that were not insignificant. This has caused the state to make efforts to manage healththat is categorized as a disaster. Standards for health services also follow the rhythm of the victims that arenot small every day. For this reason, it is necessary to examine whether the risk of spreading a pandemicin health is part of legal protection and whether a pandemic is part of disaster mitigation that receives legalprotection. The linkage to health protection during the pandemic and law as the basis for policies to be ableto implement health decisions and policies, which certainly requires effective and fast treatment.